Implementation of Islamic Education Values in the Character Development of Prospective Madrasah Teachers through Interactive E-Module Learning Based on Flip Builder - Rosdiana, Rosdiana (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to evaluate the practicality of using Flip Builder-based interactive e-modules to foster Islamic character among prospective Madrasah teachers within the framework of Islamic education. This study employs both qualitative and quantitative descriptive approaches, with a focus on practicality and effectiveness testing. The research participants consisted of students of the Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) and lecturers from the Faculty of Tarbiyah and Teacher Training. The practicality of the e-module was assessed through user response questionnaires and direct observation of its use in online and offline learning. The results showed that e-modules have a high level of practicality, with 98% of students and 95% of lecturers giving positive responses. The practicality of the e-module is supported by its high accessibility, compatibility with various digital devices, and flexibility across different learning contexts. Therefore, Flip Builder-based interactive e-modules have proven to be effective and practical as a learning medium for integrating Islamic values in the education of prospective Madrasah teachers and supporting the development of Islamic character.